Uveitis associated with rifabutin and macrolide therapy for Mycobacterium avium intracellulare infection in AIDS patients. Issue 6 (December 1996) - Kelleher, P; Helbert, M; Sweeney, J; Anderson, J; Parkin, J; Pinching, A
Abstract : OBJECTIVE: Uveitis has been increasingly recognised as a side effect of rifabutin regimens in the prophylaxis and treatment of Mycobacterium avium intracellulare (MAI) infection. This study describes the clinical features and analyses the factors associated with rifabutin induced uveitis. DESIGN: Retrospective observational study. SETTING: Tertiary care institution, The Royal Hospitals NHS Trust, London. PATIENTS: 68 HIV seropositive individuals receiving rifabutin for prophylaxis or treatment of MAI infection. RESULTS: 11 episodes of uveitis occurred in 10 different individuals at a median of 62 days. The disease was bilateral in four and unilateral in the remainder. All subjects experienced ocular pain and photophobia and 9 individuals had a significant reduction in visual acuity. Uveitis was treated with mydriatics and topical steroids and resolved in all cases when rifabutin was stopped. The risk of uveitis was significantly increased with concurrent clarithromycin therapy, Odds Ratio 13.08, 95% Confidence Interval 1.98 to 83.12. CONCLUSION: Rifabutin can cause a reversible uveitis. This risk is increased with concurrent clarithromycin therapy. Adverse drug interactions can be an important cause of morbidity in patients with advanced HIV disease.